2016
DOI: 10.1016/j.rmed.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of COPD in primary care; gender differences and the role of spirometry

Abstract: These results may suggest a difference between genders in some of the clinical features of COPD and a difference in likelihood of a GPs provisional diagnosis of COPD being correct. The study reiterates the absolute importance of spirometry in the diagnosis of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
15
2
1
Order By: Relevance
“… 27 In general, COPD is more prevalent in males. 28 , 29 However, in our study, most of the subjects were female, and the results of our study could be related to the occupation of the subjects. The majority of the respondents were nurses, and there is a possibility that they were more interested in having their health status investigated than were doctors.…”
Section: Discussioncontrasting
confidence: 54%
“… 27 In general, COPD is more prevalent in males. 28 , 29 However, in our study, most of the subjects were female, and the results of our study could be related to the occupation of the subjects. The majority of the respondents were nurses, and there is a possibility that they were more interested in having their health status investigated than were doctors.…”
Section: Discussioncontrasting
confidence: 54%
“…Regardless of these findings, the study demonstrated that there was an overall stability in statewide hospitalisation for COPD over the 5 years from 2010 to 2015 with the highest incidence occurring among metropolitan males, and contrary to previous research or projections . Further, it was highlighted that hospitalisation rates among rural females aged 65 years and over were significantly higher than their metropolitan counterparts, and consistent with the globally observed increase in the prevalence of COPD in females …”
Section: Discussioncontrasting
confidence: 49%
“…12 Further, it was highlighted that hospitalisation rates among rural females aged 65 years and over were significantly higher than their metropolitan counterparts, and consistent with the globally observed increase in the prevalence of COPD in females. 24 Overall, metropolitan males aged 85 or more years of age had the highest hospitalisation rates than all age groups and cohorts, and males aged 75 years and older were consistently higher than other cohorts of the same age. However, rural females shared a similar incidence rates with metropolitan males until the age of 75 year or older when rural female hospitalisation rates steadily decreased until they paralleled rural males and metropolitan females over the age of 85 years.…”
Section: Discussionmentioning
confidence: 88%
“…These differences are seen prospectively in randomized trials and cohort studies, both in primary care and specialized care. Although in lesser amount, sex differences have been studied regarding respiratory symptoms or diseases ( 9 , 27 , 28 ). However, no studies were performed in the Netherlands and the only study we found in primary care focussing on respiratory complaints has been performed in Spain with significantly fewer patients than this cohort study ( 9 ).…”
Section: Discussionmentioning
confidence: 99%